1993
DOI: 10.1016/0266-7681(93)90023-9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Upper Arm and Forearm Tourniquet Tolerance

Abstract: This study examined the use of upper arm and forearm tourniquets for hand surgery. 40 subjects (20 males, 20 females) were randomly assigned to one of four groups: left upper arm, left forearm, right upper arm and right forearm. Tourniquets were applied to these areas. Subjects were asked to rate their discomfort at 10-minute intervals and the total time of tourniquet tolerance was recorded. The results of a three-factor ANOVA revealed no statistically significant differences in either pain rating or tournique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 3 publications
2
23
0
Order By: Relevance
“…Reports in the literature are conflicting. Yousif et al 2 concluded that patients tolerate tourniquets on the upper arm and forearm equally well, whereas Hutchinson and McClinton 3 found that a tourniquet on the forearm was tolerated longer and was considered to be less painful, both while it was inflated and immediately after release. Our aim was to determine if a tourniquet on the forearm has advantages over one on the upper arm.…”
mentioning
confidence: 99%
“…Reports in the literature are conflicting. Yousif et al 2 concluded that patients tolerate tourniquets on the upper arm and forearm equally well, whereas Hutchinson and McClinton 3 found that a tourniquet on the forearm was tolerated longer and was considered to be less painful, both while it was inflated and immediately after release. Our aim was to determine if a tourniquet on the forearm has advantages over one on the upper arm.…”
mentioning
confidence: 99%
“…Although the tourniquet has been traditionally placed at the upper arm, the efforts to reduce cost and improve efficiency led to studies that investigated the convenience of using forearm or wrist tourniquets. [1][2][3][4][5][6][7][8][9] Conflicting reports have been published comparing upper arm and forearm settings with regards to total tourniquet time until discomfort, pressure limits, breakthrough bleeding, and other complicating events. 2,4 -9 There are studies in favor of using forearm tourniquets instead of upper arm tourniquets, with the claim that they are tolerated better and longer without pain, and that they carry a lower risk of local anesthetic side effects and nerve palsies.…”
Section: Results: Twenty Volunteers Aged 20mentioning
confidence: 99%
“…The common parameters for comparison were scales of patient discomfort and pain, and clinical variables such as blood pressure and pulse. [1][2][3][4][5][6][7][8][9] The biochemical indicators of tissue ischemia and its byproducts, the level of oxygenation, and end products of metabolism have never been used for comparison.…”
Section: Results: Twenty Volunteers Aged 20mentioning
confidence: 99%
“…It can be placed on the arm or the forearm. Several studies have shown the tourniquet is better tolerated when placed at the forearm [6][7][8]. In order to reduce the disadvantages associated with tourniquet use, a forearm-specific, sterile, single-use, nonpneumatic tourniquet has been recently introduced on the market (Hemaclear 1 Model-F).…”
Section: Discussionmentioning
confidence: 99%